First record of Ochthebius (s. str) minabensis Ferro, 1983 (Coleoptera, Hydraenidae) from Turkey - Kasapo?lu, Ahmet; Erman, Orhan; Erman, Ömer Köksal (My University, 2004)
Ochthebius (s. str) minabensis Ferro, 1983 is recorded from Turkey for the first time. Its identification according to our specimens and distribution around the world is reviewed. © TÜBITAK.
Keywords: Coleoptera; First record; Hydraenidae; Ochthebius; Taxonomy; Turkey